Blood Pressure and Heart Rate-Related Ratios as Predictors of Cardiovascular Diseases: A Comprehensive Review - Abdulaziz Amin Al Baqshi et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Blood pressure (BP) and heart rate (HR) are vital parameters widely utilized in assessing cardiovascular health. Beyond these standalone measures, derived indices such as pulse pressure (PP), mean arterial pressure (MAP), and heart rate variability (HRV) offer significant insight into cardiovascular disease (CVD) risk. This comprehensive review examines the role of BP and HR-related ratios—such as systolic-to-diastolic BP ratio, HR-to-BP ratio, and HRV—in predicting the onset and progression of CVDs. The review highlights recent research findings, clinical implications, and future prospects for utilizing these parameters in preventive cardiology. Received Date: November 05, 2024 Accepted Date: November 26, 2024 Published Date: December 01, 2024 Available Online at https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/269 https://doi.org/10.5281/zenodo.14278574